Sufficient conditions for uniform exponential stability and h-stability of some classes of dynamic equations on arbitrary time scales. (May 2019) - Ben Nasser, Bacem; Boukerrioua, Khaled; Defoort, Michael; Djemai, Mohamed; Hammami, Mohamed Ali; Laleg-Kirati, Taous-Meriem
Abstract: This paper investigates the exponential stability and h -stability problems of some classes of nonlinear systems. First, we analyze the global uniform exponential stability for a class of integro-differential equations on time scales. We also derive some sufficient conditions for stability using an integral inequality approach. Then, we give an analysis of the h -stability of some classes of linear systems under Lipschitz-type disturbances. To this end, some h -stability criteria are established. Finally, numerical examples are proposed to illustrate the stability concepts.